A CONSTRUÇÃO SOCIAL DA JUVENTUDE RURAL DIANTE DOS PROCESSOS MIGRATÓRIOS: UM ESTUDO DE CASO DA AGRICULTURA FAMILIAR DE ITAPURANGA-GO - Laila Mayara Drebes (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
Internal and international migrations have taken place in the brazilian family farming, affecting especially the rural youth. This study examined the implications of migration on the social construction of rural youth and its consequences on the family farming. In terms of methodology, the research was conducted in the case study format and held in the city of Itapuranga, state of Goiás, in March 2014. Data were collected through semi-structured interviews with social workers involved in migration and also bibliographic research, documentary research and unsystematic observations. The transformations in the socialization of young people triggered the construction of a migrant rural youth, whose social horizons were expanded from the local to the global limit with the emergence of international migration along the internal migration. These migrations also favored emptying, aging and masculinization of family farming, causing difficulties in social reproduction. In summary, migrations have shown new ways to live the youth in rural areas and transformed the existing social relationships, requiring a different perspective of development.